Structures, spectroscopy and modeling of a rare set of isomeric copper(II) complexes - Comba, Peter; Pandian, Shanthi; Wadepohl, Hubert; Wiesner, Sebastian (Inorganica chimica acta, 2011)
The structures and spectroscopic properties of various conformations of two diasteromeric pairs of enantiomers of pentacoordinate CuII bispidine complexes with chiral tetradentate ligands are reported. With one of the ligands an interesting type of distortional isomerism was observed experimentally, and this was studied in detail on the basis of the experimental structural and spectroscopic data (UV-Vis-NIR, EPR) and a DFT-, MM- and ligand-field-theory-based analysis.
Available online 27 February 2011
Gesehen am 07.04.2022